Students’ Experience of Online Interpreting Learning with Native Speakers - Budiati, Budiati; Nurjanah, Ratih Lalily; Hardiany, Dewi Rosnita (Jurnal Ilmu Sosial dan Humaniora, 2024)
Interpreting is one of the skills that is very necessary in global communication. The use of digital technology and web-based technology in interpreting classes has been widely used in Indonesia, especially during the COVID-19 pandemic. Learning interpreting is very challenging, especially directly with native speakers and done using e-learning. This research aims to describe the experience of online interpreting learning with native speakers from the student's perspective regarding the problems and advantages of this learning method. This research was qualitative in nature, involving all sixth semester students in the English Literature study program who took Interpreting Workshop course totaling 25 students. Data were obtained through observation and questionnaires. The finding of the study shows learning interpreting online with native speaker has several advantages as well as it has less psychological impact. It is hoped that after finding problems, solutions can be found to overcome these problems and utilize the advantages of this learning method to maximize learning outcomes.